Income diversification of Chinese rural households after they rent out land - Ming Guan (Cogent Business & Management, 2016)
Economic reforms in China have created opportunities for rural households pursue different types of livelihood strategies to source income from a combination of income-earning activities. A number of rural households rent out their land and choose income diversification strategies. It is speculated that these strategies might be closely interrelated, but proper statistical tests are lacking. Using China Family Panel Studies data, we identify influencing determinants of income diversification activities of Chinese rural households. This paper first examines the factors that determine the participation of farm households in one business activity, using three separate logit regressions. Seemingly unrelated bivariate probit regression (SURBP) is used to examine the factors that determine the participation of farm households in two income activities, and investigates whether the participation in them influences one another. This paper uses a multivariate probit model (MVP) to reflect the fact that in practice, Chinese rural households simultaneously consider the use of various business activities. Using data from a large-scale household survey, results from bivariate probit regression suggest that business activities are influenced one another insignificantly. The results from MVP indicate that simultaneous business activities take poor effect. Finally, some feasible policies are suggested.
Keywords: 650